Réponses

2014-06-04T00:21:09+02:00
Bonsoir,

f(x)=x^2 -3x + 7\Longrightarrow \boxed{f'(x)=2x-3}\\\\f(x) = - 3x^2 + 5x - 1\Longrightarrow \boxed{f'(x)=-6x+5}\\\\f(x) =x^3 + 5x^2\Longrightarrow \boxed{f'(x)=3x^2+10x}\\\\; f(x) = 2x^3 - 4x + 6\Longrightarrow \boxed{f'(x)=6x^2-4}\\\\f(x) = \dfrac{x^2}{4} - \dfrac{x}{\sqrt{2}}\Longrightarrow f'(x)=\dfrac{2x}{4}-\dfrac{1}{\sqrt{2}}\Longrightarrow \boxed{f'(x)=\dfrac{x}{2}-\dfrac{\sqrt{2}}{2}}\\\\f(x) = x^2 - \dfrac{3}{4}\Longrightarrow \boxed{f'(x)=2x}
Merci pour les réponses. J espere m ensouvenir pour le ccf de demain.